Comparative study of various methods for extraction of multi- quantum wells Schottky diode parameters. (October 2020) - Garoudja, Elyes; Filali, Walid; Oussalah, Slimane; Sengouga, Noureddine; Henini, Mohamed
Abstract: In this work, forward current voltage characteristics for multi-quantum wells Al0.33 Ga0.67 As Schottky diode were measured at temperature ranges from 100 to 300 K. The main parameters of this Schottky diode, such as the ideality factor, barrier height, series resistance and saturation current, have been extracted using both analytical and heuristics methods. Differential evolution (DE), particle swarm optimization (PSO) and artificial bee colony (ABC) have been chosen as candidate heuristics algorithms, while Cheung technic was selected as analytical extraction method. The obtained results show clearly the high performance of DE algorithms in terms of parameters accuracy, convergence speed and robustness.